Design and control of a low-cost non-backdrivable end-effector upper limb rehabilitation device - Li, Fulan; Guo, Yunfei; Xu, Wenda; Zhang, Weide; Zhao, Fangyun; Wang, Baiyu; Du, Huaguang; Zhang, Chengkun (Frontiers in Rehabilitation Sciences, 2024)
This paper presents GARD, an upper limb end-effector rehabilitation device developed for stroke patients. GARD offers assistance force along or towards a 2D trajectory during physical therapy sessions. GARD employs a non-backdrivable mechanism with novel motor velocity-control-based algorithms, which offers superior control precision and stability. To our knowledge, this innovative technical route has not been previously explored in rehabilitation robotics. In alignment with the new design, GARD features two novel control algorithms: Implicit Euler Velocity Control (IEVC) algorithm and a generalized impedance control algorithm. These algorithms achieve O(n) runtime complexity for any arbitrary trajectory. The system has demonstrated a mean absolute error of 0.023 mm in trajectory-following tasks and 0.14 mm in trajectory-restricted free moving tasks. The proposed upper limb rehabilitation device offers all the functionalities of existing commercial devices with superior performance. Additionally, GARD provides unique functionalities such as area-restricted free moving and dynamic Motion Restriction Map interaction. This device holds strong potential for widespread clinical use, potentially improving rehabilitation outcomes for stroke patients.